Comparison of Problem-Based Learning and Lecture Methods on Teaching and Learning Satisfaction: A Quasi-Experimental Study. - Mohammadnejad, Sara; Heidarzadeh, Hamid; Pakseresht, Maryam; Vasiee, Alireza; Taheri, Safoura (Journal of Basic Research in Medical Sciences, 2025)
Introduction: Students' cognitive capacities are enhanced through the implementation of innovative pedagogical practices, which motivate them to apply their reasoning abilities to solve issues more efficiently and with better quality. Therefore, the current study was conducted to compare problem-solving learning (PBL) and lecture methods on the level of satisfaction with teaching and learning. Materials & Methods: This was a quasi-experimental research study conducted at Ilam University of Medical Sciences in 2022, involving a sample of forty emergency medical associate students selected through a convenience sampling approach and randomly allocated to control and intervention groups by dice throw. The tools included questionnaires on demographic information, satisfaction with teaching, and learning rate, which were completed before and two weeks after the end of the intervention. Descriptive and analytical tests were performed using SPSS V.16, with alpha set at 0.05. Results: The mean and standard deviation of the participants' age was 20.09±1.14. Before the intervention, there was no significant difference in learning satisfaction and learning rate between the two groups. However, after the intervention, there was a significant difference in learning satisfaction and learning rate between the two groups (P=0.003 and P=0.001). Conclusion: Teaching using problem-solving methods increased satisfaction with teaching and improved the learning rate of students.